EVALUASI KEMANDIRIAN KELEMBAGAAN PERKUMPULAN PETANI PEMAKAI AIR DI KAWASAN FOOD ESTATE LAHAN RAWA KALIMANTAN TENGAH - Yanti Rina Darsani; Yiyi Sulaeman; Masganti Masganti; Wahida Annisa Yusuf; Muhammad Noor (Jurnal Sosial Ekonomi Pertanian, 2020)
Good water management is the key to successful farming in swamp land. One of the important elements in water management is the Water User Farmers Association as the main actor that regulates water management and maintains water management infrastructure. Water User Farmers Association has an important role as a forum for learning teamwork in supporting the production process. A self-sufficient Water User Farmers Association will be able to meet its groups' needs independently. This preliminary study aims to assess the institutional structure of Water User Farmer Association in food estate area on the swampland of Central Kalimantan. The research was conducted in Belanti Siam Village and Gedabung Village, Pandih Batu District, Pulang Pisau Regency and Terusan Karya Village and Terusan Mulya Village, Betaguh District, Kapuas Regency, Central Kalimantan which were used as demfarm locations. The methodology of this research using by interviews and group discussions with management and members of farmer groups. The parameters observed include: organizational, financial, irrigation techniques (operationalization and maintenance), government support, cultivation technology, and relationships with other institutions as indicators of group independence. The results showed that the Water User Farmer Association group in the food estate area was classified as moderate independent. Efforts that need to be made to achieve a level of independence include: (i) continuous guidance and assistance from related agencies, (ii) development and enhancement of institutional capacity both in terms of organization/management and the ability of its members. The independent Water User Farmer Association institution ensures sustainability of the food estate in swampland.